Applications of Liquid Chromatography in Analysis of Pharmaceuticals and Natural Products - Oszmianski, Jan; Lachowicz-Wiśniewska, Sabina (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
It is our pleasure to present this Special Issue of Pharmaceuticals, entitled "Applications of Liquid Chromatography in Analysis of Pharmaceuticals and Natural Products". Plants produce a wide range of phytochemicals, which are secondary metabolites that confirm their identity and are used for the production of natural pharmaceuticals, among other things. The use of modern chromatographic techniques allows accurate quantitative and qualitative identification of the above-mentioned phytochemicals and their natural products. Liquid chromatography is one of the most efficient and robust specific techniques, due to the merits of convenience and strong separation ability, as well as a wide range of material applications for identification. Liquid chromatography is widely used for the analysis of plants, nutraceuticals, pharmaceuticals, natural product quality control, or quantitative determination of bioactive compounds. The most commonly used for the identification of different plant material and pharmaceuticals are the ultra- and high-performance liquid chromatography with UV-VIS, fluorescence, diode array, and equipped with mass spectrometry or tandem mass spectrometry detection methods. Therefore, for this Special Issue, we published works concerning the latest scientific news, insights, and advances in the field of innovation and applications of liquid chromatography in the analysis of phytochemicals and natural products.